FOXO1 transcription factor modulates airway epithelial responses to viral infection - Nadia M. Daniel; Ritu Mann-Nüttel; Nami Shrestha Palikhe; Joaquin López-Orozco; Tom Hobman; Paul Forsythe; Harissios Vliagoftis (PLoS ONE, 2026)
The airway epithelium serves as the initial barrier of defence in the respiratory system, guarding against microbial, chemical, and environmental threats introduced through inhaled air. Pattern recognition receptors within the airway epithelium facilitate the detection of these threats. Toll-like receptor-3 (TLR3), a receptor sensitive to double-stranded RNA viruses, plays a vital role in this sensing process. This study focuses on exploring the role of the Forkhead box protein O1 (FOXO1) in airway epithelial cells. While the FOXO1 transcription factor (TF) has been extensively examined in various cell types and diseases, its role in airway epithelial cells is not fully elucidated. FOXO1 expression was altered in the BEAS-2B airway epithelial cell line using a shRNA lentivirus for knockdown and a constitutively active FOXO1 plasmid (CA-FOXO1) for overexpression. Confirmation of FOXO1 knockdown/overexpression was achieved through qRT-PCR, immunofluorescence, and Western blotting. FOXO1 activity was impeded using the FOXO1 inhibitor AS1842856 in BEAS-2B and normal human bronchial epithelial (NHBE) cells. TLR3 expression was assessed through qRT-PCR and Western blot. Inflammatory cytokines/chemokines IL6, CXCL10, TSLP, CCL26, IL8, GM-CSF, IFN-λ1, TNF-α and CCL2 were analyzed using MSD Immunoassays after stimulation with TLR3 ligand Poly(I:C). ECIS analysis demonstrated that FOXO1-deficient airway epithelial cells exhibit enhanced recovery of barrier integrity following wounding, with faster restoration and higher resistance compared to control cells. FOXO1-deficient BEAS-2B cells exhibited reduced TLR3 mRNA expression while cells transfected with constitutively active FOXO1 displayed increased TLR3 mRNA expression, without corresponding changes in TLR3 protein levels. Inhibition of FOXO1 activity reduced TLR3 mRNA expression in BEAS-2B and NHBE cells. Co-treatment of BEAS-2B cells with the FOXO1 inhibitor and Poly(I:C), resulted in lower IL6 and CCL2 release compared to stimulation with Poly(I:C) alone, but did not affect the release of the other cytokines/chemokines measured. Finally, Poly(I:C) stimulation induced a time-dependent increase in FOXO1 nuclear localization in airway epithelial cells. FOXO1 depletion had no effect on RIG-I, MAVS, or MYD88 expression, suggesting selective regulation of TLR3 among antiviral RNA-sensing pathways. FOXO1 inhibition in SARS-CoV-2–infected NHBE cells significantly reduced viral spike RNA levels 24 h post-infection. Furthermore, we showed that FOXO1 knockdown did not affect cell proliferation, or cell death. In-silico analysis suggested that FOXO1 can bind to the TLR3 promoter, but our EMSA data were inconclusive. These findings indicate that FOXO1 selectively modulates airway epithelial inflammatory and barrier responses. FOXO1 inhibition may have therapeutic potential in mitigating airway inflammation. However, further studies are needed to elucidate the underlying mechanisms of FOXO1-mediated TLR3 regulation.